Rancang Bangun Sistem Penetapan Angka Kredit dengan Metode Rapid Application Development - Maulana, Sabrian; Khaira, Ulfa; Hutabarat, Benedika Ferdian (TIN: Terapan Informatika Nusantara, 2025)
The manual process of determining employee credit scores often leads to issues such as administrative complexity, human error, and low transparency. This study designs a web-based information system to digitize the process efficiently. The Rapid Application Development (RAD) method is employed to accelerate system iteration and testing. Key features include credit score submission, role-based data validation, change history tracking, and activity logs as an audit trail. The workflow is illustrated using a multi-actor activity diagram involving employees, the HR division, and management. The system is designed with a focus on security, efficiency, and data integration. Testing was conducted using a black-box approach to ensure that all functionalities operate as intended. Results show that the system performs optimally, remains stable, and is responsive across various usage scenarios. Therefore, this system contributes as a digital solution that improves accuracy, efficiency, and accountability in the credit score determination process, which is a critical component of personnel management, particularly within government and educational institutions.